To compare different non-surgical treatment modalities on treatment of obstructive sleep apnea: A systematic review and meta-analysis - Jyotsna Vimal; Pranjali Dutt; Nishi Singh; Balendra P Singh; Pooran Chand; Sunit Jurel (Wolters Kluwer Medknow Publications, 2022)
The study aimed to assess the effect of mandibular advancement device (MAD) in patients with obstructive sleep apnea for reduction in 24-h mean blood pressure, sleep quality, Apnea Hypopnea Index (AHI), and patient compliance, compared to continuous positive airway pressure (CPAP), other interventions, or no treatment. Three different databases such as PubMed, EMBASE, and CENTRAL were searched using different search terms till July 2021 as per the inclusion and exclusion criteria. After inclusion of studies, data extraction including risk of bias assessment was done. For each study, we used odds ratio, mean difference, and 95% confidence interval to assess and synthesize the outcomes. The quality of evidence was evaluated as per the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE). Twenty-one randomized controlled trials were included: 497 patients in the MAD group, 239 patients in the CPAP group, and 274 patients in the sham group. In MAD-CPAP comparison, the results favored CPAP in the reduction of AHI of 3.48 (1.76-5.19). However, unclear results were found for sleep quality measured as Epworth Sleepiness Scale (ESS), patient compliance, and 24-h mean blood pressure. In MAD-sham comparison, the results favored MAD in the reduction of AHI of − 8.39 (−10.90-−5.88] and ESS of − 0.91 (−1.70-−0.12) and favored sham in terms of patient compliance while, unclear results for 24-h mean blood pressure. The GRADE score indicated that the quality of evidence is very low, low, and moderate for different outcomes. CPAP in comparison to MAD and MAD in comparison to sham showed a significant AHI reduction. However, patient compliance and 24-h mean blood pressure were not significantly different in MAD-CPAP or MAD-sham. Quality of evidence is very low and low when MAD was compared with CPAP and sham, respectively, for AHI.